Contents tourism and local community revitalization: the case of Hida-Furukawa as an anime sacred site for 'Your Name' - Reyes, Maria Corazon C. (Quezon City Asian Center, University of the Philippines Diliman, 2022)
Amidst Japan's population and labor dilemma, tourism became a significant resource to help revitalize its economy. Japan is a tourism nation, capitalizing on its cultural industry and large consumer market. Under the concept of content-induced tourism, a specific phenomenon of anime tourism is recognized and embodied in national economic policymaking, mainly touted in the "Cool Japan Strategy". Today, Japan's tourism in major cities has considerably developed, but the impact of tourism in the rural setting is relatively understudied.

In 2016, the anime film, Kimi no Na Wa or in English "Your Name" became a global success. The fictional town of Itomori is modeled after the small town of Hida-Furukawa in Gifu prefecture and became known for its anime sacred sites for the film. The town thereafter saw an influx of anime pilgrims. This study aims to understand the anime tourism phenomenon that occurred in Hida-Furukawa by exploring and analyzing the narratives of participation of the residents and the local government's tourism plans.

The study describes the actors in anime tourism and determines its influence that underpins local revitalization in a rural town. It shows that tourism in Hida-Furukawa is unsustainable and suffers a boom-and-bust pattern, wherein tourism experiences a surge and decline once the anime's popularity fades. However, the touristification and the locality's participation in tourism generate a distinct branding of Hida as a travel destination. Moreover, because tourism involves exchanges between actors, it leaves a lasting effect on the people-to-people exchange between locals, domestic and overseas tourists. The tourism phenomenon influences a more globalized perspective for the residents, while simultaneously promoting their local culture.

This study aims to contribute to anime tourism studies and in general to Japan's contemporary tourism studies. --Provided by the author.
Thesis (Master of Arts in Asian Studies)--University of the Philippines Diliman, June 2022
Keywords: Contents tourism -- Japan; Popular culture -- Social aspects -- Japan; Animated films -- Japan